Analysis of gallbladder cancer treatment and results: about 175 observations - Melogno, Silvio; Estefan, Alberto; Portos, Ruben (Cirugía del Uruguay, 1972)
The treatment of gal!bladder cancer in 175 patients and the results obtained, are analyzed. This series, because of the number of case histories involver, is the third in the world literature. Only 3 patients are still ali ve after 5 years ( 1.7 % ) ; the average rate. of survival of patients subject to paliative procedures was 2.7 months and of those explored, 1.5 months. R. Smith's indications, with modifications, are discussed together with therapeutic conduct adapted to each situation in the light of present knowledge of biology and treatment of gallbladder cancer.